Comparison of Different Types of Oral Adsorbent Therapy in Patients with Chronic Kidney Disease: A Multicenter, Randomized, Phase IV Clinical Trial - Kee, Youn Kyung; Han, Sang Youb; Kang, Duk-Hee; Noh, Jung Woo; Jeong, Kyung Hwan; Kim, Gheun-Ho; Kim, Yang Wook; Kim, Beom Seok (Yonsei medical journal, 2021)
Oral adsorbents delay disease progression and improve uremic symptoms in patients with chronic kidney disease (CKD). DW-7202 is a newly developed oral adsorbent with high adsorptive selectivity for uremic toxins. We evaluated patient preference for and adherence to DW-7202 versus AST-120 therapy and compared treatment efficacy and safety in patients with pre-dialysis CKD. A seven-center, randomized, open-label, two-way crossover, active-controlled, phase IV clinical trial was conducted. Patients with stable CKD were randomly assigned to receive DW-7202 (capsule type) or AST-120 (granule type) for 12 weeks. The groups then switched to the other adsorbent and took it for the next 12 weeks. Patient preference was the primary outcome. Secondary outcomes included changes in estimated glomerular filtration rate (eGFR) and serum creatinine, cystatin C, and indoxyl sulfate (IS) levels. Significantly more patients preferred DW-7202 than AST-120 ( <0.001). Patient adherence improved after switching from AST-120 to DW-7202; there was no apparent change in adherence after switching from DW-7202 to AST-120. Changes in eGFR and serum creatinine, cystatin C, and IS levels were not significantly different according to adsorbent type. There was also no significant difference in the incidences of adverse events during treatment with DW-7202 and AST-120. DW-7202 can be considered as an alternative to AST-120 in patients who cannot tolerate or show poor adherence to granule type adsorbents. Further studies to evaluate factors affecting patient preferences and improved adherence are warranted (Clinical trial registration No. NCT02681952).